Optimization of sample cleanup procedure for determination of diarrhetic shellfish poisoning toxins by use of experimental design - Aase, Brit; Rogstad, Astri (Journal of Chromatography A, 1997)
In routine monitoring of diarrhoeic shellfish poison (dinophysistoxin-1 and okadaic acid) there appeared to be an inconsistency between the mouse bioassay and existing chemical analysis based on liquid chromatography. The sample cleanup procedure has been subject to minor modifications in an effort to overcome the problem. However, further studies have appeared necessary and in this study all experimental factors that can influence the sample cleanup using solid-phase extraction columns prior to the LC analysis have been evaluated by use of experimental statistical design in order to understand the effect of the various factors and to optimize the conditions for recovery of the toxins. Based on our experiments we suggest using a solid-phase extraction silica column of 100 mg in the sample cleanup procedure and washing solvents composed of dichloromethane instead of chloroform to minimize the effect of stabilizing alcohol. It is sufficient to apply 7.5 ml hexane–dichloromethane (1:1) to the column in the first washing step and 2.5 ml of dichloromethane in the final washing. Elution is complete by use of 2.5 ml chloroform with 3.5% methanol. Toxic shellfish tested by this procedure confirmed the mouse bioassay.